An Adjunct Treatment Reverses Insulin-dependent (Type 1) Diabetes in a Teenager - Yap, Steve (International Journal of Biotechnology for Wellness Industries, 2015)
Globally, more than 30 million people suffer from diabetes mellitus type 1 (T1DM) characterized by pancreas producing little or no insulin hormone to facilitate glucose entering cells for energy production. T1DM patients tend to suffer a higher overall rate of atherosclerosis, cancer, and end-stage renal failure. No drug or surgical therapy seems to halt its annual upward trend amongst children and young adults. Consequently, a significant number of sufferers turn to complementary or alternative therapies for help to arrest this chronic endocrine condition. This paper discusses how a well-designed evidence-based dietary and nutritional therapy with some lifestyle modifications might offer a solution for this highly complex autoimmune disorder. The treatment outcome demonstrated a partial regeneration of pancreatic islet beta cells with substantial improvement for all relevant serum and urine markers tested.